The orientalism in the thinking of Marx and Engles - Badleh, galal; almohammad, Mohsen (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This paper is interested in the quest for the arguments of orientalist thinking in the texts of the Marxism founders. It’s trying to provide an answer to a three dimensional question that can be resumed as follows: Could the thinking of Marx and Engels be inscribed within the orientalist occidental cultural system or should it be placed out of it? Or maybe it’s neither out of this orientalist system nor inside it, but rather are there some orientalist tendencies that didn’t get to be a constant unhesitating orientalist position. Moreover, we will try to perform an epistemological reading following the steps of the French philosopher Althusser when we announce the death of the texts in which penetrates the ideology of orientalism because they contradict with the materialist conception of history, that is to say, we admit the rupture between the texts that treated the Orient and in which appeared the orientalist conceptions (fixed characters,Eurocentrism) and the other texts from which this orientalist ideology was absent.